An efficient environmentally friendly CuFe2O4/SiO2 catalyst for vanillyl mandelic acid oxidation in water under atmospheric pressure and a mechanism study. (24th December 2020) - Mao, Haifang; Wang, Hongzhao; Meng, Tao; Wang, Chaoyang; Hu, Xiaojun; Xiao, Zuobing; Liu, Jibo
Abstract : Aimed at the green production of vanillin, a highly efficient environmentally friendly oxidation system was introduced to oxidize VMA with a porous CuFe2 O4 /SiO2 component nano-catalyst in aqueous solution under atmospheric pressure. Abstract : With the aim of the green production of vanillin, a highly efficient environmentally friendly oxidation system was introduced to oxidize vanillyl mandelic acid (VMA) with a porous CuFe2 O4 /SiO2 component nano-catalyst in aqueous solution under atmospheric pressure. The N2 adsorption–desorption pattern indicated that CuFe2 O4 /SiO2 possessed a much higher specific surface area (49.98 m 2 g −1 ) than that of CuFe2 O4 (5.02 m 2 g −1 ), which further indicated that the SiO2 substrate restrained the aggregation of CuFe2 O4 nanoparticles. The conversion for VMA and selectivity for vanillin reached 98% and 96%, respectively, under atmospheric pressure. The excellent catalytic performance was attributed to the synergistic effect of the catalytic capacity of CuFe2 O4 and the adsorption capacity for the reactant of SiO2 . Simultaneously, the effect of different reaction conditions for catalyst activity and selectivity were investigated. Furthermore, the probable mechanism of VMA oxidation was investigated by in situ ATR-FTIR, H2 -TPR, XPS and 1 H NMR. More importantly, the decarboxylation was verified to proceed in basic conditions rather than in conventional acidic conditions.